Inheriting Digital Legacies: Navigating Grief and Engaging With the Past - Widmaier, Lorenz (My University, 2025)
This dissertation provides fundamental empirical insights into how a digital legacy affects and shapes grief, mourning, and remembrance today, and outlines implications for the bereaved and professionals. It addresses a gap in empirical research on personal bereavement and memory in relation to digital legacies, in particular on private practices of grieving and remembering. The research sample comprises 33 media-elicitation interviews with bereaved persons, photographs, screenshots, and social media contents. The purpose of this constructivist grounded theory study is to contribute to empirically based research on digital legacies and to provide inspiration and initial guidance to bereaved people and professionals. The findings reveal a profound impact of digital legacies on grief, mourning, and remembrance. They demonstrate that the fundamental quality of a digital legacy is its capacity to document both the intimate details and the ordinary routines of everyday life, and suggest that this leads to novel opportunities for recalling the past, reconstructing the past, and maintaining digital bonds. However, the findings also reveal challenges related to access, posthumous privacy, and distressing digital legacies. While the study examines the role of digital legacies in a variety of bereavement cases, it finds that digital legacies play a special role in cases of suicide and can be instrumental in suicide postvention. Implications for practice relate to aspects of digital legacy planning, digital legacy management, and digital legacy practices. The study may be relevant to bereaved people, professionals working in the fields of death and bereavement, researchers in the interdisciplinary field of bereavement studies, and anyone interested in the impact of new technologies on bereavement and memory.
Keywords: fundamental empirical insights; digital legacy